Cooperating Congregations: Portraits of Mission Strategies - Waldkoenig, Gilson; Avery, William (Rowman & Littlefield Publishers, 2000)
Based on an intensive study of five cooperative ministry ventures, this thought-provoking book looks at how each takes a unique approach in addressing its own mission context. From rural ministries in North Dakota and West Virginia, to ambitious community development projects in Alabama and Maine, to intensive urban mission in Milwaukee, these engaging stories will stimulate readers to take a fresh look and new approaches to parish and community issues.